PENGARUH JUMLAH SUDU TERHADAP UNJUK KERJA 3D PRINT TURBIN AIR TIPE VORTEX - Alvin Dio Nugroho; Purbo Suwandono; Dadang Hermawan; Arief Rizki Fadhillah (TURBO [Tulisan Riset Berbasis Online], 2022)
The potential of natural resources in the form of water energy is a renewable natural resource that is often used because it does not damage the environment and can be used continuously. This water flow has two types, namely laminar flow and turbulent flow, the forces generated from these two flows are also different. Turbulent flow tends to produce a greater force and can lift object masses better than laminar flow. Therefore, a vortex turbine has emerged which utilizes turbulent flow as a waterwheel drive, by directing laminar flow towards the cross section and converting it into turbulent flow by utilizing the force of gravity and The cross-sectional shape forms a whirlpool that can move a waterwheel and turn a turbine. The number of blades is very influential on the performance generated from the vortex turbine and affects the resulting output, be it voltage, current, rotational speed, torque and efficiency. In this study, the best results were shown on blades with a total of 6, at a rotational speed of 141.3 rpm; at the voltage shows the result of 0.28 volts; at current it produces 44 mA; at Torque (Nm) 0.22 Nm; and the efficiency is 76.5%.